PENINGKATAN SAVING KWH DAN PENEKANAN SUSUT NON-TEKNIS MELALUI OPTIMALISASI P2TL DI PT PLN (PERSERO) ULP MUARA TEBO - Mardini Hasanah; Pipit Puspitasari; Surya Ramadan; Herris Yamashika (Rang Teknik Journal, 2026)
Electricity is an essential need in almost all human activities, making it a vital component of everyday life. However, in the process of distributing it to customers, there is often a difference between the energy delivered and the energy sold, known as energy loss or shrinkage. This shrinkage can be categorized into two types, namely technical and non-technical shrinkage. PT PLN (Persero) uses the Jogja formula to map and analyze these two types of shrinkage, allowing a percentage comparison between technical and non-technical shrinkage. The focus of this research is on efforts to overcome non-technical shrinkage, especially in Muara Tebo ULP. PT PLN (Persero) implements preventive measures, including public education on the efficient and safe use of electrical energy, as well as the routine implementation of the Electricity Usage Control (P2TL). The purpose of these measures is to reduce non-technical losses that occur in the use of electricity. The results of the P2TL implementation in ULP Muara Tebo showed an increase in average kWh generation from 193,193 kWh in the January to May period to 216,582 kWh in June. This increase contributed significantly to the reduction of total shrinkage by 2.51% in June. This research confirms that a structured enforcement and education strategy can effectively improve energy distribution efficiency and reduce non-technical losses, supporting the overall operations of PT PLN (Persero).Keywords: energy loss, non-technical loss, formula jogja, P2TL